Book Reviews: Introduction - Kauffman, Robert J. (Institutional Knowledge at Singapore Management University, 2000)
New technological innovations in electronic commerce (EC) challenge even the most experienced corporate strategists to successfully position their organizations in the changing business environment. This special section of book reviews showcases titles that are intended to provide insights into EC-related strategy formulation at four different levels of analysis.